Plan de negocio para la industrialización y exportación de pasta de cacao orgánico hacia Alemania - Lasso Garzón, Diana Estefanía (2013)
The Ecuador has traditionally been cocoa producer and is now recognized internationally. Global trends for the preservation and care of the environment takes the idea of marketing a product that allows Ecuadorian expand our idea of exporting only raw materials and let other countries are recognized for their end products. Achieving export cocoa derivatives as organic cocoa paste and in the future also are recognized worldwide for its derivatives and final product. With on market intelligence, it was found that demand in Germany is high, and there is an acceptance of the product, but the amount of organic cocoa currently cannot meet the demand, which is a major challenge, however government programs are supporting farmers with training to have a better quality product and increase yields, representing a growth opportunity for the project. To enter to the German market was established as a central strategy of differentiation that is not exported as a product that offers the same benefits. According the market research this product has to be selling by direct sales, as well as participation in international fairs. It will feature key personnel and qualified to perform their duties, with plans set for optimizing company resources. The estimated initial investment of the project is USD 921,967.29 for the project implementation. Under a normal scenario, with a leverage ratio of 46%, at a rate of 11.83%, get an Internal Rate of Return-IRR of 3% and a Net Present Value- NPV of USD 90,895.40 which demonstrates the financial viability of the project